Analisis moderasi inklusi keuangan pada pengaruh platform terhadap minat penggunaan pinjaman online - Prajogo, Uke; Rusno, Rusno (MBR (Management and Business Review), 2023)
The aim of this research is to analyze the moderation of financial inclusion on the influence of platforms on interest in using online loans. The research sample was 50 SMEs who were members of ABM Preneur using a stratified random sampling technique. The research results show that H1 is supported but H2 is not supported. So the platform has a significant positive effect on interest in using online loans. However, financial inclusion does not moderate the influence of the platform on interest in using online loans.